Protective Effect of the Aqueous Extract of Deschampsia antarctica (EDAFENCE®) on Skin Cells against Blue Light Emitted from Digital Devices - Silvia Lorrio; Azahara Rodríguez-Luna; Pablo Delgado-Wicke; Marta Mascaraque; María Gallego; Azahara Pérez-Davó; Salvador González; Ángeles Juarranz (International Journal of Molecular Sciences, 2020)
Skin is being increasingly exposed to artificial blue light due to the extensive use of electronic devices. This, together with recent observations reporting that blue light—also known as high-energy visible light—can exert cytotoxic effects associated with oxidative stress and promote hyperpigmentation, has sparked interest in blue light and its potential harmful effects on skin. The photoprotective properties of new extracts of different botanicals with antioxidant activity are therefore being studied. Deschampsia antarctica (Edafence®, EDA), a natural aqueous extract, has shown keratinocyte and fibroblast cell protection effects against ultraviolet radiation and dioxin toxicity. In this regard, we studied the protective capacity of EDA against the deleterious effects of artificial blue light irradiation in human dermal fibroblasts (HDF) and melanocytes. We analyzed the impact of EDA on viability, cell morphology, oxidative stress, melanogenic signaling pathway activation and hyperpigmentation in HDF and melanocytes subjected to artificial blue light irradiation. Our results show that EDA protects against cell damage caused by artificial blue light, decreasing oxidative stress, melanogenic signaling pathway activation and hyperpigmentation caused by blue light irradiation. All these findings suggest that EDA might help prevent skin damage produced by artificial blue light exposure from screen of electronic devices.